A call for action that cannot go to voicemail: Research activism to urgently improve Indigenous perinatal health and wellbeing. Issue 4 (July 2021) - Hickey, Sophie; Roe, Yvette; Ireland, Sarah; Kildea, Sue; Haora, Penny; Gao, Yu; Maypilama, Elaine Läwurrpa; Kruske, Sue; Campbell, Sandy; Moore, Suzanne; Maidment, Sarah-Jade; Heinemann, Kayla; et al.
Abstract: In this call to action, a coalition of Indigenous and non-Indigenous researchers from Australia, Aotearoa New Zealand, United States and Canada argue for the urgent need for adequately funded Indigenous-led solutions to perinatal health inequities for Indigenous families in well-resourced settler-colonial countries. Authors describe examples of successful community-driven programs making a difference and call on all peoples to support and resource Indigenous-led perinatal health services by providing practical actions for individuals and different groups.